The impact of the simultaneous networking training classroom teachers to instill in the initial application efficiencies of continuous assessment - Al-Zahrani, Saleh Ali (Journal of Educational and Psychological Sciences, 2019)
The aim of the study was to identify the effectiveness of simultaneous network training in providing the teachers of the primary grades some of the competencies of the application of continuous evaluation. The researcher used the "Semi-Experimental Method". The study population is one of the primary school teachers in the schools of the Education Bureau in Qalwa Governorate. The study population is 150 teachers. The sample of the study is 30 teachers. The researcher used the observation as a tool for this study, A tribal observation, and a remote observation. Statistical processing was done with spss, repetitive tables, percentages and arithmetic mean. The results of the study are the most important of which are the effectiveness of simultaneous network training in the development of activating the teachers of the first grades of the continuous evaluation of their multiple variables and their effective use within the classrooms. We conclude that the effect of the independent variable "concurrent network training" on the dependent variable " May range from (0.89,0,97). The most important recommendations of the study are the design of training programs similar to the teachers in all disciplines and at all educational levels, simultaneous networking in the provision of continuous guidance and guidance and overcoming difficulties in applying the system of continuous evaluation according to its correct mechanisms and in light of specific criteria that can be referred to continuously. Contributes to overcoming traditional training problems.